2020
DOI: 10.1101/2020.02.06.936302
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Freshwater monitoring by nanopore sequencing

Abstract: Clean freshwater lies at the heart of human society and monitoring its quality is paramount. In addition to chemical controls, traditional microbiological water tests focus on the detection of specific bacterial pathogens. The direct tracing of all aquatic DNA poses a more profound alternative. Yet, this has hitherto been underused due to challenges in cost and logistics. Here we present a simple, fast, inexpensive and comprehensive freshwater diagnostics workflow centred around portable nanopore DNA sequencin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 84 publications
0
11
0
Order By: Relevance
“…Using Minimap2 (Li, 2018), we aligned our nanopore sequencing reads against the three different publicly available databases, NCBI 16S RefSeq, RDP and SILVA. Performance matrix comparison of thirteen different classification tools by Urban and colleagues revealed that Minimap2 provided robust alignments that were closely aligned to their mock community taxa (Urban et al, 2020). However, similar to the challenges encountered by Urban et al (2020), we have had issues of high memory usage on Minimap2, which necessitated a reduction in the number bases loaded into memory to process in the query batch (command -K 100M).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using Minimap2 (Li, 2018), we aligned our nanopore sequencing reads against the three different publicly available databases, NCBI 16S RefSeq, RDP and SILVA. Performance matrix comparison of thirteen different classification tools by Urban and colleagues revealed that Minimap2 provided robust alignments that were closely aligned to their mock community taxa (Urban et al, 2020). However, similar to the challenges encountered by Urban et al (2020), we have had issues of high memory usage on Minimap2, which necessitated a reduction in the number bases loaded into memory to process in the query batch (command -K 100M).…”
Section: Discussionmentioning
confidence: 99%
“…Performance matrix comparison of thirteen different classification tools by Urban and colleagues revealed that Minimap2 provided robust alignments that were closely aligned to their mock community taxa (Urban et al, 2020). However, similar to the challenges encountered by Urban et al (2020), we have had issues of high memory usage on Minimap2, which necessitated a reduction in the number bases loaded into memory to process in the query batch (command -K 100M). By comparing against a defined mock community, we observed differences in the taxonomic assignments between the databases-with the NCBI 16S RefSeq database clustered at 100% providing the most accurate assignments, which could be attributed to the differences in the database size and sequence validation steps (Balvočiūtė & Huson, 2017;Park & Won, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The described data processing and read classification steps were implemented using the Snakemake workflow management system ( Köster and Rahmann, 2012 ) and are available on Github - together with all necessary downstream analysis scripts to reproduce the results of this manuscript ( https://github.com/d-j-k/puntseq ; Urban et al, 2020 ; copy archived at swh:1:rev:1408d508c807b88e0989a5252c5d904072dc3c4a ).…”
Section: Methodsmentioning
confidence: 99%
“…All classification assessment steps and summary statistics were performed in R or Python ( https://github.com/d-j-k/puntseq ; Urban et al, 2020 ). We used the Python package scikit-bio for the calculation of the Simpson index and the Shannon's diversity as well as equitability index.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a work from Urban et al . [ 44 ] studied the microbial communities present in the surface water of Cam River (Cambridge). All the protocols were carried out in the lab, and the authors were able to achieve up to ∼5.5 M 16S rRNA full-length sequences with exclusive barcode assignments in a single MinION run.…”
Section: Portable Sequencing In Natural Environmentsmentioning
confidence: 99%